2014
DOI: 10.1108/jices-03-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

The engagement of social media technologies by undergraduate informatics students for academic purpose in Malaysia

Abstract: The engagement of social media technologies by undergraduate informatics The engagement of social media technologies by undergraduate informatics students for academic purpose in Malaysia students for academic purpose in Malaysia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…The particular issues that influence social interaction among individuals integrated into their technologies can be viewed from the existing literature. For instance, social interactions within households are affected by media technologies in many diverse ways (See Yin Lim et al, 2014). With regard to assisting in increasing interactions amongs families, media technologies can aid family members to help each other.…”
Section: Application Strategymentioning
confidence: 99%
“…The particular issues that influence social interaction among individuals integrated into their technologies can be viewed from the existing literature. For instance, social interactions within households are affected by media technologies in many diverse ways (See Yin Lim et al, 2014). With regard to assisting in increasing interactions amongs families, media technologies can aid family members to help each other.…”
Section: Application Strategymentioning
confidence: 99%
“…Numerous studies have been conducted among Malaysians in general and on students and young adults, in particular, in terms of their social media usage pattern, motivation as well as addictive behavior. Scholars tend to also focus on Facebook as the platform of choice due to its popularity among users (Balakrishnan & Shamin, 2013;Lim et al 2014;Moghavvemi et al, 2017;Wok et al, 2012). Other scholars like Ketab et al (2019) asserted that the development of the internet and social media has brought a new form and norm of online interaction.…”
Section: Internet Era and Interethnic Interactionmentioning
confidence: 99%
“…Like many countries, access to new forms of media is becoming widespread in Malaysia. In a recent study, it is reported that Malaysian undergraduates spend more than 6 hours online using social media technologies (Lim, Agostinho, Harper, & Chicharo, 2014). In a report from the Pew Research Centre, 70 per cent of users logged into Facebook at least once a day, and about 45 per cent logged into the site several times a day (Duggan, Ellison, Lampe, Lehnhart, & Madden, 2015).…”
Section: Reading Habits In Malaysiamentioning
confidence: 99%